The Apollo Program: giant leap or triumph of micro-innovation? - Spear, Steven J. (Henry Stewart Talks, 2019)
This case study looks closely at the development of the Apollo space program, over the eight years from the announcement by JFK that an astronaut would be sent to moon and back again, until the actual moon landing. It reveals that, contrary to the legend, the achievement was not so much a giant leap as a million tiny steps.